STUDY ON SEA LEVEL RISE IN THE WESTERN INDONESIA - Hadikusumah, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1995)
Study on mean sea level (MSL) rise has been done on tide data at some locations in the Western Indonesia. To account the effect of climate change, air temperature analyses from some weather stations are also performed. The results showed that air temperature has changed between 0.0 to 0.44°C per ten years. The sea level analysis showed that mean sea level at Western Indonesia rise between 3.10 to 9.27 mm per year. Based on the results, the prediction on mean sea level change in the years of 2000, 2030, 2050 and 2100 for Cirebon location are 17 cm, 39 cm, 55 cm, and 92 cm, respectively.